Arménie - François Verdier (In Situ)
The Armenian heritage comprises both archaeological remains of towns destroyed by never–ending wars and a number of old churches from the eleventh and twelfth centuries. Yerevan, the capital of Armenia, was founded three thousand years ago and is one of Europe’s oldest capitals. From 1925 it has developed according to an ambitious urban planning project. After the major political upheavals of 1991, a special ministry was created to look after the architectural and movable heritage of the country and to promote the Armenian national identity. A mission in Yerevan was organised by the French Heritage Direction in 1993, subsequently enabling two Armenian civil servants, a heritage curator and a technician, to work in France in 1994 and 1997. They worked in collaboration with the Regional service for cultural affairs in the Haute–Normandie region, which is developing its cultural co–operation with Armenia.